Epidemiology and patterns of lower limb injuries at a tertiary care hospital in Ahmedabad - Shakti A. Goel; Neel M. Bhavsar; Harsha Makwana; Nadeem A. Lil; Pankaj R. Patel (International Journal of Medical Research and Review, 2015)
Introduction: In the recent era of trauma, about one million people get seriously injured annually. Majority of them suffer from lower limb injuries. Due to lack of trauma registry in India, prediction models are not much effective. The aim of our study was to derive basic epidemiological parameters for lower limb injuries which can be used to develop better prediction models to reduce morbidities and mortalities.Methods: We conducted an observational study on isolated lower limb injuries without any musculoskeletal disorder at a tertiary care institution in Ahmedabad between January 2013 to October 2014. The lower limb injuries were classified as per the Limb Salvage Index score (LSI) for further management.Results: A total of 1160 patients were included. Mean age was 44.5 years and 75 percent of them were males. Lower limb injuries showed bi-modal age group with first peak between 30 to 40 years and second at 60 to 70 years. Road traffic accidents were the most common cause of injury followed by fall at home. 1.8 percent patients had Limb Salvage Index ranging between 7 to 12 and underwent amputations. Both lower limbs were almost equally affected with left showing a little higher value than right (49 versus 47 percent, p>0.05). Femur was the most commonly affected bone.Conclusion: This study helped us in identifying certain characteristics that may be useful for planning preventive strategies in an attempt to reduce the numbers of accidents and redirect public investment in health.